PUBLIC PERCEPTION IN CHOOSING SHARIA INSURANCE - Haris Al Amin; Muhammad Suip; Imsar; Nursyidah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This research aims to determine the influence of public perception in choosing Islamic Insurance at Kecamatan Silih Nara, Kabupaten Aceh Tengah. this research using quantitative analysis methods, the variables are public perception (x) and decision making (y), the model used in this study is a simple linear regression model that will be done after the classic assumption test which consist of a normality test and a heteroscedasticity test, using the SPSS Version 18. The data used is primary data.collected using a questionnaire who given to 100 respondents. The results of this research showed partially that public perception had a positive and significant influence in decision making to choosing Islamic Insurance at Kecamatan Silih Nara, Kabupaten Aceh Tengah. Based on the results of the t test, it was found that public perception variable obtained t – value > t – table (9,580 > 1,984), and sig. value 0,000 < 0,05. The results of the coefficient of determination test (R2) in this research are 0,484 (48,4%), which means that public perception has a 48% influence for the decision making process in choosing Islamic insurance. The results of Simple linear regression in this test is 0,695 (Positive value) which means there is a significant influence between public perception and decision making in choosing Islamic Insurane at Kecamatan Silih Nara, Kabupaten Aceh Tengah.